Strategi Public Relations Unilever Indonesia dalam Menjaga Reputasi Pasca Isu Boikot Pro-Israel - Muhammad Firman (CV. KAMPUS AKADEMIK PUBLISING, 2024)
PT Unilever Indonesia Tbk faced a crisis of product boycott calls due to pro-Israel issues that impacted the company’s reputation and performance. The background of this research is the increasing conflict between Israel and Palestine which triggered negative sentiment on social media that Unilever products are allegedly affiliated with Israel. The purpose of this research is to find out the strategies carried out by Unilever Indonesia’s Public Relations in maintaining its reputation in Indonesia. This research uses a descriptive qualitative approach with a literature study method. The results showed that Unilever Indonesia still has a fairly positive reputation and is still trusted by the Indonesian people in general. Unilever Indonesia’s Public Relations strategies, such as Strategy of Publicity and Strategy of Image, play an important role in maintaining the company’s reputation and handling the crisis well. In implication, this research shows that the right Public Relations strategy can help companies deal with crises and maintain their reputation.